A Learning by Doing Approach in the Delivery of Structural Engineering Courses of Architecture - Erkan Yazıcı, Yasemin; YAZICI, GÖKHAN (My University, 2013)
A through understanding of the principles of structural system design is particularly important for architects practising in Turkey where over 90 percent of the population reside in seismically active regions and the structures built must withstand the damaging effects of severe earthquakes. However there are problems incorporating the classroom based structural engineering courses into architectural design curriculums which are largely centered on the architectural design studio. The students of architecture are accustomed to the “learning by doing” approach used in the design studio and have a hard time adjusting to the classroom delivery of structural engineering lectures which largely use mathematical abstraction to communicate concepts of physics. This paper presents the findings of a study conducted at the Faculty of Architecture of Istanbul Kultur University to investigate the use of a “learning by doing” approach at the Building Mechanics course to increase the motivation and the academic performance of students.
Keywords: Architectural Education; Building Mechanics Instruction; Learning by Doing